2010
DOI: 10.1038/aja.2010.18
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genistein and equol on human and rat testicular 3β-hydroxysteroid dehydrogenase and 17β-hydroxysteroid dehydrogenase 3 activities

Abstract: The objective of the present study was to investigate the effects of genistein and equol on 3β-hydroxysteroid dehydrogenase (3β-HSD) and 17β-hydroxysteroid dehydrogenase 3 (17β-HSD3) in human and rat testis microsomes. These enzymes (3β-HSD and 17β-HSD3), along with two others (cytochrome P450 side-chain cleavage enzyme and cytochrome P450 17α-hydroxylase/17-20 lyase), catalyze the reactions that convert the steroid cholesterol into the sex hormone testosterone. Genistein inhibited 3β-HSD activity (0.2 µmol L … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 20 publications
2
37
1
4
Order By: Relevance
“…These authors concluded that inhibition of 3 -HSD function is one of the possible mechanism through which xenoestrogens disturb spermatogenesis. In vitro studies on Leydig cells obtained from various mammals have revealed decrease in the activity and expression of 3 -HSD after OP, bisphenol A (BPA) and genistein administration (Hu et al, 2010;Kotula-Balak et al, 2011;Ye et al, 2011). Our study demonstrated that OP markedly disturbes morphology and steroidogenic function of the Leydig cells through direct effect on 3 -HSD expression and localization .…”
Section: Endocrine Disrupting Chemicalsmentioning
confidence: 74%
See 1 more Smart Citation
“…These authors concluded that inhibition of 3 -HSD function is one of the possible mechanism through which xenoestrogens disturb spermatogenesis. In vitro studies on Leydig cells obtained from various mammals have revealed decrease in the activity and expression of 3 -HSD after OP, bisphenol A (BPA) and genistein administration (Hu et al, 2010;Kotula-Balak et al, 2011;Ye et al, 2011). Our study demonstrated that OP markedly disturbes morphology and steroidogenic function of the Leydig cells through direct effect on 3 -HSD expression and localization .…”
Section: Endocrine Disrupting Chemicalsmentioning
confidence: 74%
“…It is worth noting that the effect of EDCs on HSDs function can be diverse depending on the choice of animal species, age, routes of administration and dose levels. Studies of PogrmicMajkic et al (2010) have shown that in rat Leydig cells atriazine stimulated 17 -HSD, whereas other authors reported inhibition of these enzyme in rat and human microsomes treated with various xenoestrogens (Hu et al, 2010;Vaithinathan et al, 2008;Ye et al, 2011). Recently, it has also been found that antiandrogens such as tributylin, triclosan and flutamide modified HSDs expression in Leydig cells and microsomes of various mammals (Kim et al, 2008;Kumar et al, 2009;McVey & Cooke, 2003;Ohno et al, 2005;Ohsako et al, 2003).…”
Section: Endocrine Disrupting Chemicalsmentioning
confidence: 94%
“…In animal studies, correlations have already been made between phytoestrogen intake, androgen decrease and ED. 37,[65][66][67] In the light of this evidence, it is important to bridge the lacunae in the understanding of this sexual health threat to men through well-designed epidemiological and prevalence studies.…”
Section: Oestrogenic Provocation From the Environmentmentioning
confidence: 99%
“…While these flavonoids might enhance StAR gene expression by reducing the transcriptional repressor DAX-1 protein, they might inhibit the positive effect of calciumdependent signaling on StAR gene expression; 2) Inhibitory effects of flavonoids on steroidogenic enzymes. It was reported that some of the flavonoids are able to inhibit activities of the enzymes involved in testosterone biosynthesis (Figueiroa et al, 2009;Hu et al, 2010). These inhibitory effects may reduce the efficacy of flavonoid-enhanced testosterone production; 3) Levels of cAMP in Leydig cells.…”
Section: Potential Application Of Natural Flavonoids In Delaying the mentioning
confidence: 99%